A fast and fatal course of bronchiectasis: an unusual rare expression of chronic graft versus host disease. A case report - Labžentytė, Violeta; Zemnickienė, Silvija; Danila, Edvardas; Šileikienė, Virginija; Zablockis, Rolandas; Gruslys, Vygantas (Acta medica Lituanica, 2016)
Introduction. We report a case of a patient with acute myeloid leukaemia whose treatment with bone marrow transplantation (BMT) was followed by chronic graft versus host disease (GVHD) with lung involvement and bronchiectasis. This report illustrates an unusual course of a fast progression of the bronchiectasis due to BMT. Case description. A  33-year-old female was diagnosed with acute myeloid leukaemia. An allogeneic BMT was performed. One month after the  transplantation, acute GVHD with skin involvement occurred. Treatment with prednisolone and mycophenolate mofetil (MMF) has been started. Nine months later, the patient was examined by a pulmonologist due to progressive dyspnoea. A pulmonary computed tomography (CT) scan showed normal parenchyma of the lungs and no changes to the bronchi. A CT scan performed 7 months later revealed bronchiectasis for the first time. No clinical response was associated with the treatment and the patient’s respiratory status progressively deteriorated. During the  final hospitalization, a CT scan performed 1 year later revealed huge cystic bronchiectasis in both lungs. Despite the prophylaxis and treatment of GVHD and aggressive antimicrobial therapy, the patient died one year after the diagnosis of bronchiectasis. Conclusions. This case demonstrates that a fast and fatal course of bronchiectasis, that occurs after BMT, should always be considered as a possible manifestation of chronic graft versus host disease (cGVHD) following allogeneic BMT.
Keywords: bronchiectasis; bone marrow transplantation; chronic graft versus host disease; computed tomography